2015
DOI: 10.1097/md.0000000000001607
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of HPA Axis Function After Successful Gonadotropin-Induced Pregnancy and Delivery in a Woman With Panhypopituitarism

Abstract: Hypopituitarism is defined as the partial or complete defect of anterior pituitary hormone secretion. Patients with hypopituitarism usually need life-long hormone replacement therapy. However, in this case, we report a patient with panhypopituitarism whose hypothalamus–pituitary–adrenal (HPA) axis function was completely recovered after pregnancy and delivery.In this case study, we reported the case management and conducted a review of literature to identify the possible mechanism of pituitary function recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We conducted a literature search and found that successful pregnancies and deliveries have been reported in several cases of female panhypopituitarism patients over the past few decades. Surgical removal of pituitary macroadenoma, 12 corticotropic adenoma, 13 and suprasellar germinoma 14 are the main causes of panhypopituitarism, while successful pregnancies and deliveries, either spontaneously or by assisted reproduction, have not yet been reported in female PSIS patients. A population‐based study on pregnancy outcomes in women with panhypopituitarism revealed a higher risk of maternal infection and congenital anomalies in these women.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a literature search and found that successful pregnancies and deliveries have been reported in several cases of female panhypopituitarism patients over the past few decades. Surgical removal of pituitary macroadenoma, 12 corticotropic adenoma, 13 and suprasellar germinoma 14 are the main causes of panhypopituitarism, while successful pregnancies and deliveries, either spontaneously or by assisted reproduction, have not yet been reported in female PSIS patients. A population‐based study on pregnancy outcomes in women with panhypopituitarism revealed a higher risk of maternal infection and congenital anomalies in these women.…”
Section: Discussionmentioning
confidence: 99%
“…We searched the literature and found that several cases of successful pregnancies and deliveries were reported in panhypopituitarism female patients in the past few decades. Panhypopituitarism was mainly caused by surgical removal of pituitary macroadenoma [15], corticotropic adenoma[16], and suprasellar germinoma [17], while successful pregnancies and deliveries either spontaneously or by assisted reproduction were still not found in PSIS female patients. The results of a population-based study on pregnancy outcomes in women with panhypopituitarism showed that the risk of maternal infection and congenital anomalies was higher in women affected by panhypopituitarism, and no signi cant differences were found in the risk of developing gestational hypertension, gestational diabetes mellitus, placental abruption, preterm delivery, small for gestational age or other pregnancy complications [18].…”
Section: Discussionmentioning
confidence: 99%
“…We selected 17 papers that met the objectives of our research and the exclusion criteria (Figure 1). In all case reports in the literature, except that of I. Lata [11], pregnancy has occurred thanks to techniques of ARTs [13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). However, success rate was lower than in other unovulatory infertility.…”
Section: Discussionmentioning
confidence: 99%